구성원의 보상과 직무만족의 관계: 상사의 지원과 지각된 내적 공정성의 역할 탐색 - 장옥진; 이정언; Teo, Yit Chin; Lee, Jeong Eon (한국콘텐츠학회 논문지, 17(6), 2017)
The main purpose of this research is to investigate the impact of compensation on job satisfaction. The study is designed to determine whether perceived internal equity acts as a mediation role in affecting the relationship between compensation and job satisfaction. This study also aims to explore the role of supervisor support in affecting employees' perception of equity toward the compensation. A total of 157 samples was obtained for the data analysis as a quantitative approach. The results of the data analyses revealed that both extrinsic and intrinsic rewards are positively correlated with job satisfaction. The results also showed that perceived internal equity acts as a mediating role in predicting variables of compensation and job satisfaction. The supervisor support does not moderate the relationship between compensation and perceived internal equity. It is suggested that management's efforts must be made in compensation management in order to increase employees' job satisfaction and to improve employees' perception of equity. 본 연구는 기업 조직구성원에 대한 보상이 내적공정성과 직무만족에 미치는 영향을 분석하는 것을 목적으로 하였다. 보상의 요인은 내적 보상과 외적 보상의 두 하위차원으로, 내적 공정성은 분배공정성과 상호 작용 공정성으로 구분하였다. 이와 더불어 기업 구성원에 대한 보상이 상사의 지원에 따라 지각된 내적 공정성이 달라질 수 있는지 그 조절 효과를 분석하였다. 실증연구는 다양한 기업의 157명으로부터 획득된 자료를 활용하여 이루어졌다. 실증자료의 분석 결과, 외적 및 내적 보상은 직무만족, 지각된 내적 공정성, 상사의 지원에 정(+)의 영향을 미쳤으며, 보상과 직무만족의 관계는 구성원의 심리적 영역인 내적 공정성의 지각을 통해 영향관계가 형성되고 있음이 나타났다. 한편 구성원에 대한 보상과 지각된 내적 공정성의 관계에서 상사의 지원은 조절역할을 하지 않는 것으로 밝혀졌다. 본 연구에서는 보상관리의 중요성에 대한 인식을 바탕으로 보상의 공정성에 주목하여 개인간 상대적인 보상 차이에 대한 합리적인 논리와 메커니즘을 제공하여야 한다는 관리적 실천적 시사점을 제공하였다.